Evaluation of an evidence-based medicine educational intervention in a regional medical campus - Mylene Levesque (Canadian Medical Education Journal, 2018)
Background: Enhanced educational activities were developed by a regional medical campus (RMC) in order to incorporate evidence-based medicine (EBM) practice in the learning process of medical students. This study aimed to measure the effectiveness of these activities. Methods: The experimental group was made up of third-year students from the RMC. The comparison group included students from the main campus of the medical school and another of its RMCs. The experimental group received additional training on EBM: one additional hour in class, plus skills development exercises throughout the semester. During the regular academic sessions, clinical questions requiring EBM literature searching skills were incorporated in the curriculum. Tests on knowledge and self-assessment of competencies were administered to all participants at the beginning and at the end of the semester. Data were analyzed using repeated measures analysis of variance and post hoc tests for within and between groups comparison. Results: The Friedman test demonstrated a statistically significant effect of the intervention on knowledge (p <0.0001). The score of the knowledge test was significantly higher for the experimental group, when compared with baseline testing and with the comparison group (p <0.0001). Repeated measures analysis of variance demonstrated a statistically significant effect of the intervention on the score of the self-assessment of competencies (p=0.032). The score for the self-assessment of competencies was significantly higher for the experimental group when compared to baseline score (p <0.0001), but not with respect to the comparison group. Conclusion: Our study demonstrated the effectiveness of additional training and longitudinal integrated skills development leading to an increase in medical student knowledge and self-perception of competencies in EBM practice.